A revision of loasoid Caiophora (Caiophora pterosperma-group, Loasoideae, Loasaceae) from Peru - Ackermann, Markus; Weigend, Maximilian (Phytotaxa, 2013)
Caiophora is a taxonomically difficult, nearly exclusively Andean genus of the largely South American family Loasaceae subfam. Loasoideae. Elevational distribution and flower morphology argue for a relatively basal position of loasoid Caiophora in the genus. Caiophora has not been revised since 1900, and details of their morphology, distribution and species delimitation are incompletely understood. The Caiophora pterosperma-group clearly belongs to Caiophora based on habit, fruit morphology, karyology and molecular data, but is florally similar to members of the closely allied genera Loasa and Scyphanthus. The Peruvian members of the Caiophora pterosperma-group are here revised. Three species are recognized: C. pterosperma, endemic to the departments of Junín and Pasco (including C. smithii, C. serropetala and C. pavonii), C. stenocarpa from the departments Cuzco and Huancavelica, and the new species Caiophora dederichiorum, endemic to the department of Ancash. All three species occur at low elevations for the genus (down to 2200 m a.s.l.) and in seasonally dry habitats, unlike most representatives of the genus (usually found in mesic habitats at higher elevations). A key to the Peruvian members of the group, diagnoses, drawings and photographs are provided for all species recognized.